Probabilistic Entity-Relationship Models, PRMs and Plate Models - Heckerman, David; Meek, Chris; Koller, Daphne (Introduction to Statistical Relational Learning, 2004)
We introduce a graphical language for relational data called the probabilistic entityrelationship (PER) model. The model is an extension of the entity-relationship model, a common model for the abstract representation of database structure. We concentrate on the directed version of this model—the directed acyclic probabilistic entity-relationship (DAPER) model. The DAPER model is closely related to the plate model and the probabilistic relational model (PRM), existing models for relational data. The DAPER model is more expressive than either existing model, and also helps to demonstrate their similarity.